Al-Qīmah al-Sulūqiyah fī Qissah Mūsa wa Khidir - Chaterina Puteri Doni; Saida Gani; firafitara firafitara (Universitas Muhammadiyah Gorontalo, 2022)
The purpose of this research procedure is to know the intrinsic elements of the story of moses and khidir in surah al-kahfi, and to know the moral value of the story of the prophet moses and khidir in surah al kahfi. The research methods used are qualitative and descriptive research, and the method used in collecting materials is the library. From the results of the study, there are several things that researchers obtain the existence of intrinsic elements consisting of title/theme, characters, settings/places, plot/plot, point of view and language style, and the existence of behavioral values such as sincerity, patience, persistence, strength and so on. Researchers found seven behaviors namely, humility, strength, obedience, discipline, patience, manners, and confidence.